New material concepts - Nunes, J. P. (2020)
This chapter focuses on new compositions of thermoplastic matrices and reinforcements to process by fused deposition modelling (FDM). The available materials for this additive manufacturing (AM) technique are generally limited to PLA—polylactic acid, ABS—acrylonitrile butadiene styrene and PA—polyamide NYLON®)with temperature gradients and mechanical behaviours that are not suited for high-performance applications, such as aeronautics and automotive sector. In this work, an intensive research was made in order to evaluate mechanical, thermal and rheological properties considered important for 3Dprinting of commercial filaments. Results aided in the selection of high-performance reinforced materials for AM. Advanced polymers, such as PEEK—polyether ether ketone and PA66—polyamide 66, were the matrices chosen to produce high service nanocomposite formulations, each with varying amounts of multi-wall carbon nanotubes (MWCNTs). The resulting feedstock materialswere characterized using the same techniques as the commercial filaments. Preliminary tests with printed parts of these composites were made in pursuance of their optimal printing parameters to undergo an experimental hybrid system (EHS).